TPEN induces apoptosis independently of zinc chelator activity in a model of acute lymphoblastic leukemia and ex vivo acute leukemia cells through oxidative stress and mitochondria caspase-3- and AIF-dependent pathways (2012)
ABSTRACT: Acute lymphoblastic leukemia is still an incurable disease with resistance to therapy developing in the majority of patients. We investigated the effect of TPEN, an intracellular zinc chelator, in Jurkat and in ex vivo acute lymphoblastic leukemia (ALL) cells resistant to chemotherapy. Changes of nuclei morphology, reactive oxygen species generation, presence of hypodiploid cells, phosphatidylserine translocation, mitochondrial membrane depolarization, immunohistochemical identification of cell death signalling molecules, and pharmacological inhibition were assayed to detect the apoptotic cell death pathways. We found that TPEN induces apoptosis in both types of cells by a molecular oxidative stress pathway involving O2->H2O2>> NF-κB (JNK/c-Jun) > p53 > m > loss caspase-3, AIF > chromatin condensation/DNA fragmentation. Interestingly, TPEN induced apoptosis independently of glucose; leukemic cells are therefore devoid of survival capacity by metabolic resistance to treatment. Most importantly, TPEN cytotoxic effect can eventually be regulated by the antioxidant N-acetyl-cysteine and zinc ions. Our data suggest that TPEN can be used as a potential therapeutic prooxidant agent against refractory leukemia. These data contribute to understanding the importance of oxidative stress in the treatment of ALL.